Ethiopia’s Great Transition : The Next Mile - A Country Economic Memorandum - World Bank (Washington, DC : World Bank, 2022)
Ethiopia’s rapid growth over the past two decades has resulted in a surge in income per capita levels, with the country approaching fast the middle-income milestone. Over the past decade, fast growth was driven by capital accumulation, but the extent to which this growth has been equally distributed is unclear. Public infrastructure spending accelerated dramatically in the first half of the 2010s, helping underpin fast economic growth. However, this approach seems to have had important shortcomings. Contrary to the findings of World Bank (2015) which examined an earlier period, total factor productivity (TFP) declined during 2011-2020, contributing negatively to growth. In addition, inequality at the household level increased between 2011 and 2016. Finally, macroeconomic imbalances have widened, a trend exacerbated by recent shocks. This report discusses the drivers of growth in Ethiopia and, in the absence of official subnational gross domestic product (GDP) figures, examines whether there has been convergence in economic activity at the subnational level.